(untitled) - Jostein Lindland (Rome, Italy, 1997)
The book offers knowledge about the impact of the Uruguay Round (UR) on tariff escalation in the agricultural sector. Tariff escalation has been one of the obstacles for developing countries in their efforts to establish processing industries for exports. In addition, the book takes into account both specific and ad valorem tariffs that may be applied on the input and output products
Keywords: agricuture - uraguay - economic aspects,uraguay - economic conditions